Preparation method of core-shell Ni-MOF-coated MnFe-PBA material

Through the preparation method of core-shell Ni-MOF@MnFe-PBA material, the lattice matching limitation is overcome, and the preparation of a high-specific capacitance MOF-on-MOF heterostructure is achieved, and the MOF-on-in- in the prior art is solved. The problem of limited application of MOF materials has wide applicability and efficient electrochemical properties.

CN119285981APending Publication Date: 2025-01-10YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523204.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing preparation methods for MOF-on-MOF type heterogeneous composite materials are limited by the lattice matching requirements between the MOF matrix and the secondary MOF particles, which limits their wide application.

Method used

Using the preparation method of core-shell Ni-MOF@MnFe-PBA material, solution A is formed by dissolving ferric chloride, manganese chloride tetrahydrate, and polyvinylpyrrolidone in a mixed solution of ethanol and deionized water. Ni-MOF and potassium hexacyanoferrate were dissolved in deionized water to sonicate to form solution B. Then solution A was added dropwise to solution B. The reaction product was collected by centrifugation, washed with ethanol and freeze-dried to obtain core-shell MOF -on-MOF heterostructure.

Benefits of technology

This method does not require functional modification of MOF, breaking away from the limitations of the lattice matching principle, the prepared material has high specific capacitance, is suitable for a variety of PBA materials, the synthesis conditions are controllable, and has universal applicability and industrial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285981A_ABST
    Figure CN119285981A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a core-shell type Ni-MOF (at) MnFe-PBA material, which comprises the following steps: preparing Ni-MOF; the preparation method comprises the following steps: dissolving ferric chloride, manganese chloride tetrahydrate and polyvinylpyrrolidone in a mixed solution of 20 mL of ethanol and 20 mL of deionized water, and stirring for a certain time to obtain a solution A; ni-MOF and potassium hexacyanoferrate are dissolved in 20 mL of deionized water, ultrasonic treatment is conducted for a certain time, and a solution B is formed; dropwise adding the solution A into the solution B, stirring for 2 hours, and carrying out centrifugal collection, ethanol washing and freeze drying on a reaction product for 3 hours; by means of the MOF-on-MOF type heterogeneous composite material core-shell Ni-MOF-coated MnFe-PBA prepared through the method, the strict requirement for lattice matching between an MOF matrix and secondary MOF particles can be eliminated, and the composition, the structure and the application of the MOF-on-MOF heterostructure can be further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and specifically relates to a method for preparing a core-shell Ni-MOF@MnFe-PBA material. Background Art

[0002] Nanohybrid materials containing multiple components show new physical and chemical properties beyond their constituent components in important applications such as catalysis, sensing, gas adsorption and separation, energy storage and conversion. Metal-organic frameworks (MOFs) are a type of crystalline network structure formed by inorganic metal nodes and organic ligands periodically connected by coordination bonds. MOFs are ideal synthetic platforms for building multi-component systems due to their modular and versatile chemical properties as well as their tunable size and morphology. Combining MOFs with other specific components such as nanoparticles, polymers, and biomolecules is an effective strategy for constructing MOF-based multi-component systems with versatility and high complexity. These combinations cascade components with different properties and functions to form composite materials with complex components and multiple integrated functions, showing unique application prospects in many fields.

[0003] Recently, coupling two or more MOFs with different properties into multi-component MOFs or multi-component MOFs to construct MOF-on-MOF heterogeneous composite materials has become a research hotspot in the fields of chemistry and materials. Among them, the epitaxial growth method is the most commonly used and most intensively studied synthesis method for constructing MOF-on-MOF heterogeneous composite materials. This method is to epitaxially grow another MOF on a MOF or other crystal template according to the principle of optimal lattice matching to form a common MOF-on-MOF composite with precise arrangement. However, since most MOFs have different components and mismatched lattice structures, the strict lattice matching principle limits the widespread application of the epitaxial growth method. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the problems existing in the preparation of MOF-on-MOF type heterogeneous composite materials in the above-mentioned and / or prior arts, the present invention is proposed. The MOF-on-MOF type heterogeneous composite material core-shell Ni-MOF@MnFe-PBA prepared by the present invention can get rid of the strict requirements on lattice matching between the MOF matrix and the secondary MOF particles, which helps to further expand the components, structure and application of MOF-on-MOF heterogeneous structures.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a core-shell Ni-MOF@MnFe-PBA material, comprising the following steps: Preparation of Ni-MOF; Dissolve ferric chloride, manganese chloride tetrahydrate, and polyvinyl pyrrolidone in a mixed solution of 20 mL ethanol and 20 mL deionized water, and stir for a certain period of time to obtain solution A; Ni-MOF and potassium hexacyanoferrate were dissolved in 20 mL of deionized water and ultrasonicated for a certain period of time to form solution B; Solution A was added dropwise to solution B and stirred for 2 h. The reaction product was collected by centrifugation, washed with ethanol, and freeze-dried for 3 h.

[0007] As a preferred embodiment of the method for preparing the core-shell Ni-MOF@MnFe-PBA material of the present invention, the steps for preparing Ni-MOF are as follows: Nickel chloride hexahydrate, thiophene-2,5-dicarboxylic acid and sodium hydroxide aqueous solution were placed in a 25 mL high-pressure reactor, the reactor was heated at 180 °C for 61 h, and naturally cooled to room temperature. The reaction product was filtered, washed with deionized water and ethanol, and dried at 50 °C for 12 h to obtain a green powder, namely Ni-MOF.

[0008] As a preferred solution of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the amount of nickel chloride hexahydrate added is 0.36 g.

[0009] As a preferred solution of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the addition amount of thiophene-2,5-dicarboxylic acid is 0.26 g.

[0010] As a preferred solution of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the concentration of the NaOH aqueous solution is 0.2 mol / L, and the addition amount is 0.5 mL.

[0011] As a preferred solution of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the amount of ferric chloride added is 0.0036 g.

[0012] As a preferred embodiment of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the amount of manganese chloride tetrahydrate added is 0.0086 g.

[0013] As a preferred embodiment of the method for preparing the core-shell Ni-MOF@MnFe-PBA material of the present invention, the amount of polyvinyl pyrrolidone added is 0.1 g.

[0014] As a preferred embodiment of the method for preparing the core-shell Ni-MOF@MnFe-PBA material of the present invention, the addition amount of potassium hexacyanoferrate is 0.022 g.

[0015] As a preferred solution of the method for preparing the core-shell Ni-MOF@MnFe-PBA material in the present invention, the addition amount of the Ni-MOF is 0.03 g.

[0016] Compared with the prior art, the present invention has the following beneficial effects: the present invention does not require any functional modification of MOFs and is not limited by the lattice matching principle; the heterostructure material prepared by the present invention has a higher specific capacitance; the method for preparing MOF-on-MOF heterostructure material has universal applicability, not only applicable to MnFe-PBA, but also applicable to other series of PBA materials; the preparation method of the obtained core-shell MOF-on-MOF material has controllable conditions and controllable results, and the synthesis method and experimental steps are simple, which has great guiding significance in practical applications and has great industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 These are SEM images of the product Ni-MOF@MnFe-PBA in Example 1 of the present invention, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2.

[0018] Figure 2 These are the PXRD diagrams of the product Ni-MOF@MnFe-PBA in Example 1, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2 of the present invention.

[0019] Figure 3 FT-IR graphs of the product Ni-MOF@MnFe-PBA in Example 1, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2 of the present invention.

[0020] Figure 4These are the N2 adsorption isotherms of the product Ni-MOF@MnFe-PBA in Example 1, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2 of the present invention.

[0021] Figure 5 The product Ni-MOF@MnFe-PBA in Example 1, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2 in the present invention are at 20 mV s -1 The CV curve below.

[0022] Figure 6 The product Ni-MOF@MnFe-PBA in Example 1 of the present invention, the product Ni-MOF in Comparative Example 1, and the product MnFe-PBA in Comparative Example 2 were -1 GCD curves at different current densities.

[0023] Figure 7 This is the SEM image of the product Ni-MOF in Examples 2 and 3 of the present invention.

[0024] Figure 8 These are SEM images of the products Ni-MOF@MnFe-PBA (0.5C) and Ni-MOF@MnFe-PBA (2C) in Examples 4 and 5 of the present invention.

[0025] Fig. 9 CV curves of Ni-MOF@MnFe-PBA (0.5C) and Ni-MOF@MnFe-PBA (2C) in Examples 4 and 5 of the present invention.

[0026] Fig.10 GCD curves of the products Ni-MOF@MnFe-PBA (0.5C) and Ni-MOF@MnFe-PBA (2C) in Examples 4 and 5 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] Nickel chloride (NiCl2·6H2O), ferric chloride (FeCl3), manganese chloride (MnCl2·4H2O), thiophene-2,5-dicarboxylic acid (H2tdc) and potassium hexacyanoferrate (K3Fe(CN)6) used in the present invention were purchased from Aladdin, polyvinyl pyrrolidone (PVP) and sodium hydroxide (NaOH) were purchased from Meryer; ethanol (C2H5OH) was purchased from Shanghai Chemical Reagent Company; all chemicals and reagents were of analytical grade.

[0031] The preparation method of the core-shell Ni-MOF@MnFe-PBA material of the present invention comprises the following steps: Preparation of Ni-MOF; Dissolve ferric chloride, manganese chloride tetrahydrate, and polyvinyl pyrrolidone in a mixed solution of 20 mL ethanol and 20 mL deionized water, and stir for a certain period of time to obtain solution A; Ni-MOF and potassium hexacyanoferrate were dissolved in 20 mL of deionized water and ultrasonicated for a certain period of time to form solution B; Solution A was added dropwise to solution B and stirred for 2 h. The reaction product was collected by centrifugation, washed with ethanol, and freeze-dried for 3 h.

[0032] Example 1 This embodiment provides a method for preparing a core-shell Ni-MOF@MnFe-PBA material, comprising the following steps: Preparation of Ni-MOF: 0.36 g of nickel chloride hexahydrate, 0.26 g of thiophene-2,5-dicarboxylic acid and 10.5 mL of sodium hydroxide aqueous solution with a concentration of 0.2 mol / L were placed in a 25 mL high-pressure reactor, the reactor was heated at 180 °C for 61 h, and naturally cooled to room temperature. The reaction product was filtered, washed with deionized water and ethanol, and dried at 50 °C for 12 h to obtain a green powder, namely Ni-MOF; 0.0036 g of ferric chloride, 0.0086 g of manganese chloride tetrahydrate, and 0.1 g of polyvinyl pyrrolidone were dissolved in a mixed solution of 20 mL of ethanol and 20 mL of deionized water, and stirred for a certain period of time to obtain solution A; 0.03 g of Ni-MOF and 0.022 g of potassium hexacyanoferrate were dissolved in 20 mL of deionized water and ultrasonicated for a certain period of time to form solution B; Solution A was added dropwise to solution B and stirred for 2 h. The reaction product was collected by centrifugation, washed with ethanol, and freeze-dried for 3 h.

[0033] The amount of nickel chloride hexahydrate added was 0.36 g, the amount of thiophene-2,5-dicarboxylic acid added was 0.26 g, and the amount of NaOH aqueous solution added was 0.2 mol / L, 10.5 mL.

[0034] Comparative Example 1 The preparation method of Ni-MOF comprises the following steps: NiCl2·6H2O, H2TDC and NaOH aqueous solution were placed in a 25 mL autoclave, heated at 180 °C for 61 h, and cooled naturally to room temperature. The reaction product was collected by filtration, washed three times with deionized water and ethanol, respectively, and dried at 50 °C for 12 h to obtain green powder Ni-MOF.

[0035] Comparative Example 2 0.0072 g of FeCl3, 0.0172 g of MnCl2·4H2O, and 0.2 g of PVP were dissolved in a mixed solution of 20 mL of ethanol and 20 mL of deionized water, and stirred for 10 min to obtain solution A; 0.044 g of K3Fe(CN)6 was dissolved in 20 mL of deionized water and ultrasonically treated for 10 min to obtain solution B; solution A was added dropwise to solution B and stirred for 2 h. The reaction product was collected by centrifugation, washed with ethanol, and then freeze-dried for 3 h to obtain MnFe-PBA.

[0036] from Figure 1 It can be seen that in the Ni-MOF@MnFe-PBA system, MnFe-PBA is evenly distributed on the surface of Ni-MOF microrods to form a core-shell structure, indicating the successful preparation of Ni-MOF@MnFe-PBA. Ni-MOF has a microrod-like morphology with a diameter of about 1.0 μm and a length of about 7.0 μm. MnFe-PBA has a cubic morphology with a size of about 0.5 μm.

[0037] Figure 2 The characteristic diffraction peaks of Ni-MOF and MnFe-PBA are simultaneously presented, indicating the successful preparation of Ni-MOF@MnFe-PBA.

[0038] Supplementary FT-IR experiments were performed, such as Figure 3 As shown, ~3598 cm -1 The characteristic absorption peak at ~1563 cm is attributed to the stretching vibration of -OH. -1 and ~1380 cm -1 The absorption peak at ~2149cm is attributed to the asymmetric and symmetric stretching vibration of -COOH.-1 The absorption peak at ~2070 cm is the vibration of the Mn(II)-CN-Fe(III) bond. -1 The absorption peak at is attributed to the vibration of the Mn(III)-CN-Fe(II) bond. Compared with Ni-MOF and MnFe-PBA, Ni-MOF@MnFe-PBA contains the absorption peaks of the characteristic functional groups of both Ni-MOF and MnFe-PBA, which further proves the successful preparation of Ni-MOF@MnFe-PBA.

[0039] N2 adsorption experiments were carried out. Figure 4 It can be seen that the specific surface areas of MnFe-PBA@Ni-MOF, Ni-MOF, and MnFe-PBA are 63.5 m 2 g -1 、64.2 m 2 g -1 、508.8 m 2 g -1 , indicating that the specific surface area of ​​MnFe-PBA@Ni-MOF is close to that of Ni-MOF and much smaller than that of MnFe-PBA.

[0040] Electrochemical CV experiments were performed. Figure 5 It can be seen that compared with the comparison samples Ni-MOF and MnFe-PBA, the CV curve of Ni-MOF@MnFe-PBA has the largest integrated area and the strongest peak current, indicating its excellent electrochemical performance.

[0041] Electrochemical GCD experiments were performed. Figure 6 It can be seen that compared with the comparison samples Ni-MOF and MnFe-PBA, the Ni-MOF@MnFe-PBA electrode has a longer discharge time, indicating that the formed core-shell Ni-MOF@MnFe-PBA heterostructure can effectively improve the material's ability to store charge.

[0042] Example 2 This embodiment provides a method for preparing a core-shell Ni-MOF@MnFe-PBA material, which is different from Example 1 in that the NaOH aqueous solution in the raw material is 0.2 mol / L and the addition amount is 10.0 mL.

[0043] Example 3 This embodiment provides a method for preparing a core-shell Ni-MOF@MnFe-PBA material, which is different from Example 1 in that the NaOH aqueous solution in the raw material is 0.2 mol / L and the addition amount is 11.0 mL.

[0044] from Figure 7As can be seen from the middle left figure, according to Example 2, when the amount of NaOH aqueous solution added to the raw material is 10.0 mL, the prepared Ni-MOF is a block solid with uneven size, which is not conducive to the subsequent preparation of core-shell Ni-MOF@MnFe-PBA; according to Example 3, when the amount of NaOH aqueous solution added to the raw material is 11.0 mL, Figure 7 From the middle right figure, it can be observed that the size and morphology of Ni-MOF did not change significantly compared with the case when the addition amount of NaOH aqueous solution was 10. mL. Therefore, the optimal addition amount of NaOH aqueous solution for preparing Ni-MOF is 10.5 mL.

[0045] Example 4 This embodiment provides a method for preparing a core-shell Ni-MOF@MnFe-PBA material, which is different from Example 1 in that the ferric chloride in the raw materials is 0.0018 g, manganese chloride tetrahydrate is 0.0043 g, and polyvinyl pyrrolidone is 0.05 g; Ni-MOF is 0.03 g, and potassium hexacyanoferrate is 0.011 g.

[0046] Example 5 The present embodiment provides a method for preparing a core-shell Ni-MOF@MnFe-PBA material, which is different from Example 1 in that the ferric chloride in the raw materials is 0.0072 g, manganese chloride tetrahydrate is 0.0172 g, and polyvinyl pyrrolidone is 0.2 g; Ni-MOF is 0.03 g, and potassium hexacyanoferrate is 0.044 g.

[0047] from Figure 8 It can be seen from the middle left figure that according to Example 4, when the amount of ferric chloride added in the raw material is 0.0018 g, the amount of manganese chloride tetrahydrate added is 0.0043 g, and the amount of polyvinyl pyrrolidone added is 0.05 g; the amount of Ni-MOF added is 0.03 g, and the amount of potassium hexacyanoferrate added is 0.011 g, in the prepared Ni-MOF@MnFe-PBA (0.5C), only a few MnFe-PBA particles are dotted on the Ni-MOF; and according to Example 4, when the amount of ferric chloride added in the raw material is 0.0072 g, the amount of manganese chloride tetrahydrate added is 0.0172 g, and the amount of polyvinyl pyrrolidone added is 0.2 g; the amount of Ni-MOF added is 0.03 g, and the amount of potassium hexacyanoferrate added is 0.044 g, from Figure 8 In the middle right picture, it can be observed that in the prepared Ni-MOF@MnFe-PBA (2C), a large number of MnFe-PBA particles are distributed layer by layer on the Ni-MOF.

[0048] according to Fig. 9 and Fig.10Compared with Ni-MOF@MnFe-PBA (0.5C) and Ni-MOF@MnFe-PBA (2C), the integral area of ​​the CV curve of Ni-MOF@MnFe-PBA is larger, the peak current is stronger, and the GCD curve shows a longer discharge time, indicating that Ni-MOF@MnFe-PBA has better charge storage capacity. In Ni-MOF@MnFe-PBA (0.5C), too few MnFe-PBA particles have weak synergy with Ni-MOF. In Ni-MOF@MnFe-PBA (2C), too many MnFe-PBA particles are stacked and distributed on Ni-MOF, which will inhibit the active sites of Ni-MOF, so the performance of the two is poor.

[0049] In summary, Example 1 is the best embodiment. The present invention provides a method for constructing a core-shell MOF-on-MOF hybrid by anisotropically growing two MOFs with different chemical compositions and structures using intermolecular forces. The method does not involve coordination bonds at the interface of the two MOFs, thereby overcoming the strict limitations of the lattice matching principle. Using the pre-prepared Ni-MOF matrix as the seed for the nucleation and growth of the secondary MnFe-PBA particles, a core-shell MOF-on-MOF heterostructure is obtained, i.e., a MnFe-PBA shell grown on a Ni-MOF core, and the different metal centers in the two MOFs can synergize to improve the electrochemical activity. In addition, the constructed composite material can improve the charge transfer rate and the ion transfer rate. The material synthesis method provided by the present invention is simple and convenient, does not require any functionalization of MOF, and is not limited by the strict requirements of lattice matching between the MOF matrix and the secondary MOF particles.

[0050] It can be clearly seen from the above examples that Example 1 is the best implementation mode. The core-shell Ni-MOF@MnFe-PBA heterostructure was successfully prepared using the present invention, which has significant charge storage capacity and is a potential electrochemical energy storage material.

[0051] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the technical solutions of the present invention.

Claims

1. A method for preparing a core-shell Ni-MOF@MnFe-PBA material, characterized in that: The following steps are included: Preparation of Ni-MOF; Dissolve ferric chloride, manganese chloride tetrahydrate, and polyvinyl pyrrolidone in a mixed solution of 20 mL ethanol and 20 mL deionized water, and stir for a certain period of time to obtain solution A; Ni-MOF and potassium hexacyanoferrate were dissolved in 20 mL of deionized water and ultrasonicated for a certain period of time to form solution B; Solution A was added dropwise to solution B and stirred for 2 h. The reaction product was collected by centrifugation, washed with ethanol, and freeze-dried for 3 h.

2. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 1, characterized in that: The specific steps for preparing Ni-MOF are: Nickel chloride hexahydrate, thiophene-2,5-dicarboxylic acid and sodium hydroxide aqueous solution were placed in a 25 mL high-pressure reactor, the reactor was heated at 180 °C for 61 h, and naturally cooled to room temperature. The reaction product was filtered, washed with deionized water and ethanol, and dried at 50 °C for 12 h to obtain a green powder, namely Ni-MOF.

3. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 2, characterized in that: The amount of nickel chloride hexahydrate added is 0.35-0.37 g.

4. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 3, characterized in that: The added amount of the thiophene-2,5-dicarboxylic acid is 0.25-0.27 g.

5. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 4, characterized in that: The concentration of the NaOH aqueous solution is 0.2 mol / L, and the amount added is 10.0-11.0 mL.

6. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to any one of claims 1 to 5, characterized in that: The added amount of the ferric chloride is 0.0018-0.072 g.

7. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 6, characterized in that: The added amount of the manganese chloride tetrahydrate is 0.0043-0.0172 g.

8. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 7, characterized in that: The added amount of the polyvinyl pyrrolidone is 0.05-0.2 g.

9. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 8, characterized in that: The added amount of the potassium hexacyanoferrate is 0.011-0.044 g.

10. The method for preparing the core-shell Ni-MOF@MnFe-PBA material according to claim 9, characterized in that: The added amount of the Ni-MOF is 0.02-0.04 g.